Notas sobre informalidade, produtividade do trabalho e grau de utilizaç\~ao e seus impactos sobre o crescimento econômico no Brasil nos anos 2000 - Claudio Roberto Amitrano; Gabriel Coelho Squeff (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper aims at discussing the implications of informality in Brazil by presenting new evidence on value added, occupations, and in labor productivity in the formal and informal sectors, disaggregated by economic activity. Moreover, we developed counterfactual exercises for these variables in order to assess the possible impacts of labor migration from non-formal sector to the formal sector as well as from changes in the rate of capacity utilization.
Keywords: J24; O17; L16; O47; 330; labor productivity; informality; structural heterogeneity; economic growth